Pemanfaatan Krisna Funtastic Land Sebagai Sarana Leisure And Recreation Di Desa Temukus Kabupaten Buleleng - Bhaskara, Gde Indra; Ismana, Nyoman Ega (JURNAL DESTINASI PARIWISATA, 2019)
The development of tourism in Bali to date has had a positive impact on the economy of the community. In addition, tourism can increase foreign exchange and provide employment.This study contains what motivation and how the characteristics of visitors Krisna Funtastic Land and how appropriate utilization in Krisna Funtastic Land in Leisure and Recreation activities. The data used in this study are qualitative data in the form of Krisna Funtastic Land, the state of facilities and infrastructure, the history of Krishna Funtastic Land and the utilization of visitors. The result-show that the characteristics of visitors who come to Krisna Funtastic Land based on age are the majority> 20 years old, based on the area of origin originating from the Regency of Buleleng, especially the City of Singaraja, based on female sex. Based on the level of education having a high school / vocational education level, based on the type of occupation the majority are still students, based on the source of information getting information comes from friends / relations. For the appropriate utilization in Krisna Funtastic Land based on the motivation and characteristics of visitors Krisna Funtastic Land which is one of the tourist attractions in Krisna Funtastic Land, so the manager should add the game rides not only focus for children, but also for adults, The type of game rides should more be reproduced to increase the interest of tourists to visit. Keywords: Utilization, motivation and characteristics